MicroRNAs: The Missing Link in the Biology of Graft-Versus-Host Disease? - Atarod, Sadaf; Dickinson, Anne M. (Frontiers in Immunology, 2013)
Graft-versus-host disease is still the major complication of allogeneic haematopoietic stem cell transplantation. Despite extensive studies in understanding the pathophysiology of GVHD, its pathogenesis remains unclear. Recently, important functions of microRNAs have been demonstrated in various autoimmune diseases and cancers such as psoriasis and lymphoma. This review highlights the need to investigate the role of microRNAs in GVHD and hypothesizes that microRNAs may be one of the missing links in our understanding of GVHD, with the potential for novel therapeutics.